Maksim Kesantunan dalam Komunikasi Fatis Jawa Virtual: Sebuah Pendekatan Siberpragmatik - Yuli Widiana (Universitas Sebelas Maret, 2023)
Virtual communication gains popularity along with the rapid development of information technology. In a cultural context, cultural norms are employed in virtual communication. The lack of physical contact in virtual communication makes netizens utilize particular features in digital platforms to replace physical contact in performing politeness. This study explores the strategies of Javanese netizens to perform Javanese politeness maxims in virtual phatic communication. The data were taken from five WhatsApp Groups (WAG) of Javanese aged between 20s to 40s. 142 conversation texts containing phatic talks in WAG were collected by observation method. The conversational texts and virtual icons were transcribed for contextual analysis. The result shows that Javanese netizens utilized the maxims of Kurmat (Respect), Tepa Selira (Tolerance), Andhap Asor (Humility), and Empan Papan (Self-Awareness) as politeness strategies in virtual phatic communication. The tolerance maxim is the most frequently used to support each other. The maxim of humility is the least used. Javanese politeness maxims are camaraderie devices to establish social rapport in cyberpragmatics context. The employment of Javanese maxims is significant strategies to avoid conflict and the Face Threatening Act (FTA). Indeed, Javanese politeness maxims are essential in creating harmony in virtual communication.